Overheating Of The L.O Standby Pump On The Main Engine Of MT. Klawotong - Gymnastiar, Agum; Hermanto, Andy; Heriyawan, Mohammad Sapta (LPPM AKMI SUAKA BAHARI CIREBON, 2025)
The main engine Lubricating Oil (LO) standby pump is crucial for smooth ship operations. Therefore, it is essential that this equipment is well-maintained. However, future problems can arise and disrupt ship operations if the maintenance schedule is not followed. The main engine lubrication system can be disrupted due to a damaged L.O. standby pump, which can interfere with the smooth lubrication of the main engine. Based on field observation during a 12-month and 2-day sea project on board MT. Klawotong, the researcher experienced overheating of the L.O. standby pump. When the ship entered bad weather on the voyage from Wayame to Tual, it disrupted the crew's comfort on board while working. The purpose of this research is to determine the causal factors, the impact of overheating on the pump, and efforts to prevent overheating of the L.O. pump. This study uses a qualitative descriptive method by conducting interviews and direct field observations. Data analysis technique using SHEL (Software, Hardware, Environment and Liveware). By interviewing the Chief Engineer, 2nd Engineer, and 4th Engineer, this study states that overheating of the main engine L.O. standby pump is caused by a damaged rubber coupling, a damaged oil seal, and abnormal vibration in the pump. The impact of these factors will reduce pump performance, reduce lubrication in the main engine, and reduce pump performance. Preventive measures can be done by implementing routine maintenance on the pump and cleaning the oil filter regularly. Cleaning dirt adhering to the oil filter using a brush, solar, and following the procedures correctly and properly.